Availability and accessibility of public health services for adolescents and young people in South Africa. (March 2017) - Mokomane, Zitha; Mokhele, Tholang; Mathews, Catherine; Makoae, Mokhantšo
Abstract: Against the background of increasing international calls for the development and implementation of age-appropriate programmes that address both quality and access issues to improve adolescent and youth health, this paper explores the extent to which public health facilities are available and accessible to adolescents and youth in South Africa. The impetus for the study was the current evidence that there was generally poor utilisation of services offered at public health facilities by young people in the country. The overall findings are that despite the country's comprehensive legal and policy framework and commitment to improve the health of young people, there continues to be some structural and systemic factors that hamper effective provision and programming of adolescent and youth friendly services. The paper concludes with recommendations for policy and practice. Highlights: South Africa has an enabling, comprehensive and progressive legislative and policy framework for the provision of adolescent and youth friendly services in South Africa is laudable. However various provider, health facility, and programme design characteristics continue to hamper effective provision and delivery of adolescent and youth friendly health services. The need to consider the amendment of some health facility regulations such as operating hours and/or days to ensure that service provision is convenient for young people. The provision of all cadres of primary health service providers with on-going professional development and attitudinal training is imperative to break down prejudices that may limit the success of the adolescent and youth friendly programming in the country. There is need for more youth involvement in programme design and service provision.